Zygoma Fractures Are Associated With Increased Morbidity and Mortality in the Pediatric Population. Issue 2 (4th March 2021) - Elzanie, Ashraf S.; Park, Kitae E.; Irgebay, Zhazira; Choi, James; Zellner, Elizabeth G.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Trauma involving the facial bones has been shown to be associated with high severity in previous studies. Characteristics of facial fractures in adults have been well described in the adult population, less so in the pediatric literature. Our investigation aims to define these epidemiological measures and risk factors for poor outcomes using the most recent data. Methods: The 2016 Trauma Quality Improvement Program data bank was examined to study facial fracture pattern, mechanism of injury, and demographic descriptive data to characterize pediatric trauma patients. Multivariable regression analysis was performed to assess risk factors for morbidity and mortality in pediatric facial fracture patients. Results: Of 51, 168 total pediatric trauma patients, 2917 (5.7%) presented with facial fractures. Motor vehicle trauma was the most common mechanism of injury. Maxillary/malar fractures was the most common fracture type overall. Mandibular fractures were most common in the 0 to 1 age category while nasal bone fractures were more common in older patients. Patients with mandible fractures experienced the highest rate of operative management. Zygoma fracture was highly associated with concomitant traumatic brain injury. Multivariable regression analysis showed that fracture of the zygoma, concomitant traumatic brain injury, and cervical spine injury were risk factors for increased mortality. Conclusion: Facial fractures are a rare but significant form of trauma in the pediatric population. Our data suggests a slight change in fracture patterns compared to previous studies. Zygoma fractures, traumatic brain injury, and cervical spine injury are risk factors of increased mortality that clinicians should be aware of.